Reinnervation post-heart transplantation. (12th January 2017) - Grupper, Avishay; Gewirtz, Henry; Kushwaha, Sudhir
Abstract: Heart transplantation results in complete denervation of the donor heart with loss of afferent and efferent nerve connections. The majority of patients remain completely denervated during the first 6–12 months following transplantation. Evidence of reinnervation is usually found during the second year after transplantation and involve the myocardial muscle, sinoatrial node, and coronary vessels, but remains incomplete and regionally limited many years post-transplant. Restoration of cardiac innervation can improve exercise capacity as well as blood flow regulation in the coronary arteries, and hence improve quality of life. As yet, there is no evidence that the reinnervation process is associated with the occurrence of allograft-related events or survival.